Asthma in sport - Braithwaite, B. A. (Journal of Australian Strength and Conditioning, 2017)
The purpose of this paper was to provide a review of the current literature for asthma management in a sporting context and to critically appraise future management options. The information in this article was sourced from peer-reviewed articles relevant to the topic via a Google Scholar search. It appears that asthma has a high prevalence in the athletic population for all ages and that improved management may result in an improved quality of life. Asthma attacks can not only affect sporting performance, but can also result in hospitalisation or in extreme cases death. Multiple forms of improved management for acute asthma attacks and improved long-term asthma management were discussed for both the athlete themselves and for the associated staff involved. It appears that the training environment can play a large role on asthmatic symptom exacerbations. Pre-planned warm ups and closely monitored exercise may assist asthmatics in developing a greater tolerance capacity to the exercise stimulus. Internal management protocols may be of great importance for sporting clubs, including providing education regarding asthma symptoms to the athlete (and associated staff), pre-screening athletes via spirometry testing, as well as having acute management plans in place if an asthma attack was to occur. Alternative management methods such as fish oil supplementation and breathing training may provide asthmatics with an improved quality of life. In conclusion, this article highlights the importance and associated benefits/consequences of having a management plan for athletes with asthma, but also attempts to source methods for which asthmatic symptoms can be greater controlled.